Photooxidation of Methane over Au/SiO₂ catalysts under Mild Conditions - NGUYEN THI THUY HA (The Graduate School, Ajou University, 2024)
Accounting for 34 percent of natural gas, methane is a considerable component to address worldwide energy consumption. Methane conversion to functionalized-valuable products catalyzed by photocatalytic systems is promisingly hypothesized as the alternative under simultaneously harvesting solar energy. Unlike the traditional thermo-catalysis, photocatalysis can generate high energetic charge carriers under mild conditions which can activate and cleavage C-H bond of methane molecules. The spatial redox reactions within photocatalyst can prevent unnecessary radical collisions, thus further enhancing thermodynamics equilibrium aspect and suppressing the carbon dioxide generation caused by the overoxidation. As an extension of photocatalysis in the use of plasmon resonance nanoparticles (NPs), the plasmonic catalysis emerges at the interface of chemistry, plasmonic, and quantum electrodynamics in opening a brightening future to control the rates and selectivity of photocatalysis. Due to the unique optical properties, a variety of noble and non-noble metals can functionally behave as plasmonic nanomaterials (e.g. nanostructured Au, Ag, Cu). The localized surface plasmonic resonance (LSPR) effect is importantly controllable on the activity of plasmonic materials. This study presents a partial oxidation approach for the selective conversion of gaseous methane to liquid formic acid (HCOOH) while suppressing carbon dioxide production. This photoreaction capitalizes on the chemical potential inherent in charge carriers generated via interband transitions of gold nanoparticles. These energetic electron and hole carriers interact profoundly with adsorbed oxygen molecules (O₂), yielding reactive singlet oxygen (¹O₂) species. The investigation shows spin-forbidden transitions facilitated by a dexter-type electron exchange process. Remarkably, the resultant ¹O₂ species effectively reduce the energy barrier associated with C–H bond activation to 21.1 kJ mol¯¹. This process initiates the catalytic cascade following the Eley-Rideal model at ambient conditions. Consequently, it drives the preferential production of the oxygenated liquid product, HCOOH, demonstrating an impressive selectivity of > 97%.
학위논문(박사)--에너지시스템학과,2024. 2
Keywords: charge transfer; gold; interband transition; nanoparticle; partial oxidation